Into the universe with Stephen Hawking [videorecording (DVD)] - Hawking, Stephen, 1942-2018 (Gaiam, 2011)
British physicist Stephen Hawking explores the mysteries of the universe, discussing the possibility of aliens, time travel, and how the universe began.